HIV Epidemic among Pakistani Inhabitants in District Faisalabad, Pakistan - Yasmin, Riffat; Raza, Mesum; Asif, Rizwan; Khalid, Tehmina; Raza, Syed Kashif; Kalsoom, Furkhanda; Shaikh, Maida (International Health Review, 2024)
The pandemic of HIV/AIDS has severely impacted the most vulnerable sections of society in Pakistan. The results of the current study on the HIV epidemiology in Faisalabad, Pakistan, highlighted the importance of preventive measures. The current study attempted to assess the prevalence of HIV in Faisalabad. Moreover, it also identified potential risk factors for the spread of this pandemic in the region. A total of 1540 test results were gathered between March 2020 and July 2022 from 3 hospitals, that is, Allied Hospital, Aziz Fatima, and DHQ Hospital Faisalabad. Immuno-chromatographic Technique (ICT) was used to detect the presence of the infection. The researchers in District Faisalabad, Pakistan, surveyed 1540 locals to determine the HIV prevalence in that area. About 33 cases of HIV infection were confirmed through ICT, with a prevalence rate of 2.14%. Roughly, 25 males, however, only 8 females tested positive for HIV. Since more than half of HIV diagnoses occur in people between the ages of 15 and 30, it is essential that HIV prevention efforts focus on this demographic. The increased exposure to unsanitary needles and blood may explain why city dwellers appear more vulnerable than rural residents. The findings confirm that HIV is a serious threat to public health in Faisalabad, Pakistan. Community health professionals must work together to educate the public and come up with other solutions to this problem.